Bolts, shouldered, thin hexagonal head, close tolerance shank, short thread, in titanium alloy, anodized, MoS2 lubricated. Classification: 1100 MPa (at ambient temperature)/315°C. (15th February 1997) - British Standards Institution,
No abstract available